2007
DOI: 10.1103/physrevlett.98.117001
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Role of Critical Current Anisotropy on Flux Avalanches inMgB2Films

Abstract: Anisotropic penetration of magnetic flux in MgB(2) films grown on vicinal sapphire substrates is investigated using magneto-optical imaging. Regular penetration above 10 K proceeds more easily along the substrate surface steps, the anisotropy of the critical current being 6%. At lower temperatures the penetration occurs via abrupt dendritic avalanches that preferentially propagate perpendicular to the surface steps. This inverse anisotropy in the penetration pattern becomes dramatic very close to 10 K where al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
47
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 22 publications
6
47
3
Order By: Relevance
“…1. These thresholds have been explained on the basis of linear stability analysis of the nonlinear and non-local equations governing the electrodynamics of such films [15][16][17][18][19][20]. The theoretical works show that in order to trigger avalanches an electrical field in the range E = 30-100 mV/m is required.…”
mentioning
confidence: 99%
“…1. These thresholds have been explained on the basis of linear stability analysis of the nonlinear and non-local equations governing the electrodynamics of such films [15][16][17][18][19][20]. The theoretical works show that in order to trigger avalanches an electrical field in the range E = 30-100 mV/m is required.…”
mentioning
confidence: 99%
“…The most unstable mode has a finite wave-number, which means that the instability will nucleate by fingering2728293031. As the instability develops, numerical analysis of the non-linear and non-local dynamics of magnetic flux and temperature have revealed that the instabilities develop into complex branching structures2832.…”
mentioning
confidence: 99%
“…1- 23 Such patterns have been directly observed in a large number of superconducting films employing magneto-optical imaging techniques. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The existing experimental data, and the recently developed theoretical models, [14][15][16][17][18][19][20][21] suggest that the origin of these patterns is thermomagnetic instability of the vortex matter in the superconducting films. [21][22][23] The instability arises from local temperature increase due to flux motion, which, in turn, decreases flux pinning and hence facilitates further flux motion.…”
Section: Introductionmentioning
confidence: 99%